Hemophagocytic syndrome with atypical presentation in an adolescent. (11th September 2013) - Valente Pinto, Marta; Esteves, Isabel; Bryceson, Yenan; Ferrão, Anabela
Abstract : A 14-year-old adolescent presented with a prolonged fever, abnormal liver function, anaemia, thrombocytopaenia, but a good general status. Diagnosis of hemophagocytic lymphohistiocytosis (HLH) was suspected, in spite of the initial indolent course. Secondary causes were excluded, but no specific mutation indicative of primary HLH was found. The patient started with specific therapy, but progressed with reactivations and later with persistently active disease. Haematopoietic stem cell transplantation was not successful and the adolescent died 7 months after diagnosis.